2023
DOI: 10.33448/rsd-v12i3.40425
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things as support to reduce hospital errors related to medication administration

Abstract: Objective: The high potential of digital technologies to reduce medication errors in patients hospitalized or under hospital care was explored in this investigation. The study identifies common types of medication errors and their probable causes. Furthermore, examines the technological innovation solutions available that have not yet been applied in this context, specifically the Internet of Things usage to reduce medication errors through a practical example. Methods: A rapid review was applied, exploring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The third novelty of this proposal regarding the state of the art is the comparative study of the different solutions for labelling and reading data on drug packages (IoT, RFID UHF, RFID NFC and barcodes/QR), considering economic as well as operational and environmental aspects. The results improve the state of the art since existing studies do not compare the four possibilities together ( Liu et al, 2022 ; Ruan et al, 2018 ; Camacho-Cogollo, Bone & Iadanza, 2020 ; Lee et al, 2019 ; Haddara & Staaby, 2018 ; Ebrahimzadeh et al, 2021 ; Vagaš et al, 2019 ; Ko & Woo, 2018 ; Zhang, Fu & Li, 2019 ; Buthelez et al, 2022 ; Cocian, Morales & Schneider, 2023 ; Petro et al, 2009 ; Iadanza, 2012 ; Wu, Kuo & Liu, 2005 ; Bevilacqua et al, 2013 ). In contrast, this study has analysed the four technologies and has shown the advantages and disadvantages of Barcode/QR, RFID and IoT for drug management in hospitals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The third novelty of this proposal regarding the state of the art is the comparative study of the different solutions for labelling and reading data on drug packages (IoT, RFID UHF, RFID NFC and barcodes/QR), considering economic as well as operational and environmental aspects. The results improve the state of the art since existing studies do not compare the four possibilities together ( Liu et al, 2022 ; Ruan et al, 2018 ; Camacho-Cogollo, Bone & Iadanza, 2020 ; Lee et al, 2019 ; Haddara & Staaby, 2018 ; Ebrahimzadeh et al, 2021 ; Vagaš et al, 2019 ; Ko & Woo, 2018 ; Zhang, Fu & Li, 2019 ; Buthelez et al, 2022 ; Cocian, Morales & Schneider, 2023 ; Petro et al, 2009 ; Iadanza, 2012 ; Wu, Kuo & Liu, 2005 ; Bevilacqua et al, 2013 ). In contrast, this study has analysed the four technologies and has shown the advantages and disadvantages of Barcode/QR, RFID and IoT for drug management in hospitals.…”
Section: Discussionmentioning
confidence: 59%
“…However, the use of IoT for drug management in hospitals is scarce. Although some studies related to drug management and IoT have been conducted, they are focused on activities outside the hospital ( Cocian, Morales & Schneider, 2023 ). Such applications are mainly concerned with tracking the logistics of medical products ( Nanda, Panda & Dash, 2023 ) and remote monitoring of medication behaviours of patients once they have left the hospital ( Roh et al, 2021 ).…”
Section: Disruptive Information Technologies For Drug Management: Rel...mentioning
confidence: 99%